2015
DOI: 10.1590/s1806-37562015000000186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life according to asthma control and asthma severity in children and adolescents

Abstract: OBJECTIVE: To evaluate quality of life according to the level of asthma control and degree of asthma severity in children and adolescents. METHODS: We selected children and adolescents with asthma (7-17 years of age) from the Pediatric Pulmonology Outpatient Clinic of the State University of Campinas Hospital de Clínicas, located in the city of Campinas, Brazil. Asthma control and asthma severity were assessed by the Asthma Control Test and by the questionnaire based on the Global Initiative for Asthma, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
7
32
0
3
Order By: Relevance
“…In agreement with our findings, a study on Brazilian children and adolescents with asthma (7-17 years old) revealed that the activity limitation domain was lowest in comparison to other domains of the Pediatric Asthma Quality of Life Questionnaire (PAQLQ); this was more obvious in the children with poorest asthma control and greatest asthma severity. 20 Similar findings were reported as well by Josie et al in disadvantaged African American youth. 21 EQ-5D-Y performed better than other generic questionnaires such as PedsQL 4.0 which was not sensitive enough to distinguish HRQoL between children with different levels of asthma severity and control in relation physical activity.…”
Section: Discussionsupporting
confidence: 86%
“…In agreement with our findings, a study on Brazilian children and adolescents with asthma (7-17 years old) revealed that the activity limitation domain was lowest in comparison to other domains of the Pediatric Asthma Quality of Life Questionnaire (PAQLQ); this was more obvious in the children with poorest asthma control and greatest asthma severity. 20 Similar findings were reported as well by Josie et al in disadvantaged African American youth. 21 EQ-5D-Y performed better than other generic questionnaires such as PedsQL 4.0 which was not sensitive enough to distinguish HRQoL between children with different levels of asthma severity and control in relation physical activity.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, female sex was an independent risk factor for worse HRQoL. Conversely, some studies indicate that a poor asthma control is not related to sex, but to younger age and poor asthma management knowledge . However, also among children and adolescents with diabetes, another chronic disease, a worse HRQoL seems to be related to female sex and metabolic control .…”
Section: Discussionmentioning
confidence: 96%
“…5 Asthma control and asthma severity are often used to label the intensity of asthma symptoms such as wheeze, chest tightness, shortness of breath and cough. 5 Poor asthma control has a negative Meetings: Some of the results in this paper have been presented as an oral presentation, in the European Respiratory Society international congress in 2016. effect on HRQoL among children [6][7][8] and increases the risk of exacerbations among both children and adults. 9,10 Additionally, asthma severity, corticosteroid use and the number of physician visits are also previously reported risk factors for a worse HRQoL, 6 as well as allergic co-morbid conditions such as rhino-conjunctivitis and eczema.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Matsunaga et al . conducted a study with Brazilian asthmatic children and adolescents and concluded that quality of life seems to be directly related to asthma control level …”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, Matsunaga et al conducted a study with Brazilian asthmatic children and adolescents and concluded that quality of life seems to be directly related to asthma control level. 28 We used IPAQ as the only validated instrument to measure the physical activity level in asthmatic children and adolescents who were not in crisis. This may explain why we did not find an association between physical activity and asthma control level.…”
Section: Discussionmentioning
confidence: 99%